Optimal Matrix Filter Design With Application to Filtering Short Data Records - Han, Dong; Zhang, Xin Hua (IEEE signal processing letters, 2010)
This letter presents a simple computer-aided approach for designing matrix filter based on the least-square criterion. Three methods are considered for designing matrix filter. In design method 1, we minimize the normalized mean-square error between the designed and desired filter response in the passband subject to the normalized mean-square error constraint in the stopband. In design method 2, the objective function and the constraint in the design method 1 are reversed. In design method 3, the optimal matrix filter which has the general mean-square error is considered. Numerical results show that the proposed approach is effective for designing matrix filter and filtering short data records.